Kentauren in Noricum - Lamm, Susanne; Pochmarski, Erwin (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The head of a centaur found in Virunum, which is a replica of the late-Hellenistic type of the Capitoline “older centaur”, deserves special mention as a depiction of a centaur from Noricum. The extremely high-quality and dynamic centaur frieze from St. Johann near Herberstein (Hartberg – Fürstenfeld district), which originates from a aedicula-tomb, can certainly be regarded as depicting centaurs, as does a relief fragment from Hartberg, which, however, does not come from the same tomb-building. On several reliefs, a sea centaur appears as an idiosyncratic hybrid between triton and centaur, carrying a nereid on its back. These include above all two reliefs from Schloss Seggau near Leibnitz. A single relief comes from Lauriacum in northern Noricum and shows a triton or sea centaur again with a nereid.